Thermal energy storage using phase change material: Analysis of partial tank charging and discharging on system performance in a building cooling application. (5th November 2021) - McKenna, P.; Turner, W.J.N.; Finn, D.P.
Highlights: Partial charging of a phase change material thermal energy storage tank is investigated. The phase change material is water and the application is building cooling. Partial charging, compared to full charging can lead to energy efficiency gains. Higher charging and lower discharging loop flow rates give better energy performance. Charging thermal energy storage tank above 90% is not recommended. Abstract: Thermal energy storage coupled with phase change materials is a technology that offers the potential to shift and in some case reduce building cooling loads and increase energy efficiency. This simulation study uses a TRNSYS building and HVAC system model to investigate whether partially charging and discharging a phase change material thermal energy storage tank can improve the operational characteristics required by a light-weight commercial building located in a Mediterranean climate. The results indicate that partial charging and discharging can lead to better energy performance of the phase change material thermal energy storage HVAC system. If the phase change material thermal energy storage tank is not required to operate at maximum capacity (i.e., maximum charge), energy savings are possible by only partially charging the tank. Further energy efficiency gains are also possible by control of the heat transfer fluid flow rates in the HVAC thermal energy storage system loops. Generally, higher charging loop flow rates and lower discharge loop flow rates produce better energy performance. Charging a phase change material thermal energy storage tank above 90% is not recommended, as at very high charge fractions, the energy performance decreases considerably, while the charging time increases significantly.